Are Disney Characters ‘Frozen’ in Stereotypes? An Intersectional Analysis of Frozen - Rogers, Anna S. (Education Sciences & Society - Open Access, 2019)
This paper analyzes changes and continuities in the popular princess characters created by the Walt Disney Studios, specifically in the 2013 movie Frozen. The analysis focuses on five themes suggested by an intersectionality framework: the historical and geographical contexts of Disney characters; the controlling images that are revealed; the power relations among the characters; the macro and micro conditions of Disney movies; and the intersection of gender, sexuality, race, and class in the portrayed characters. The main finding is that the traditional Disney princess has made way for a new and more modern princess character that seems to transcend the conventional stereotype of former characterizations. Yet, closer inspection of the Frozen movie also shows that a new stereotype has developed that depicts a princess as someone who merely thinks she is independent, but who often still needs to rely on a man.